AKSESBILITAS PEMILU BAGI PENYANDANG DISABILITAS DI KECAMATAN KARAWANG TIMUR KABUPATEN KARAWANG PADA PEMILIHAN KEPALA DAERAH TAHUN 2020 ERA PASCA PANDEMIC COVID 19 - Martini, Nelly; Yulyana, Eka; Solehudin, Arif (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2024)
The purpose of this study is to determine the accessibility of elections for people with disabilities during the COVID-19 pandemic. This study used a qualitative descriptive method. Two types of data were used in this study: primary and secondary data, collected through interviews with key informants, non-participant observation, and literature review. Informants were selected using purposive sampling. Data analysis included data reduction, data display, and conclusion drawing/verification. The results of our research conducted during the pre-election period during the COVID-19 pandemic revealed several shortcomings on the part of election organizers. During the data matching and research process, many residents were not re-registered, resulting in some people with disabilities not being included in the disabled voter data. There were still numerous discrepancies in the disability data, and limited outreach for people with disabilities, with only one outreach activity being conducted per district. This significantly impacted voter participation in exercising their right to vote. On election day, there was a decrease in public participation in the 2020 Pilkada from a total of 1,656,024 voters with a total of 1,159,662 voters, only 70.03%, there was a decrease in public participation of approximately 10% from the previous year's election, while for disabled voters from the total data of 41 disabled voters, 36 disabled people exercised their right to vote, this shows an increase in political participation of people with disabilities.